The research progress of Chikungunya fever - Li Cai; Li Cai; Xinyi Hu; Shuang Liu; Lei Wang; Hao Lu; Hua Tu; Xibao Huang; Yeqing Tong (Frontiers Media S.A., 2023)
Chikungunya fever, an acute infectious disease caused by Chikungunya virus (CHIKV), is transmitted by Aedes aegypti mosquitoes, with fever, rash, and joint pain as the main features. 1952, the first outbreak of Chikungunya fever was in Tanzania, Africa, and the virus was isolated in 1953. The epidemic has expanded from Africa to South Asia, the Indian Ocean islands and the Americas, and is now present in more than 100 countries and territories worldwide, causing approximately 1 million infections worldwide each year. In addition, fatal cases have been reported, making CHIKV a relevant public health disease. The evolution of the virus, globalization, and climate change may have contributed to the spread of CHIKV. 2005-2006 saw the most severe outbreak on Reunion Island, affecting nearly 35% of the population. Since 2005, cases of Chikungunya fever have spread mainly in tropical and subtropical regions, eventually reaching the Americas through the Caribbean island. Today, CHIKV is widely spread worldwide and is a global public health problem. In addition, the lack of a preventive vaccine and approved antiviral treatment makes CHIKV a major global health threat. In this review, we discuss the current knowledge on the pathogenesis of CHIKV, focusing on the atypical disease manifestations. We also provide an updated review of the current development of CHIKV vaccines. Overall, these aspects represent some of the most recent advances in our understanding of CHIKV pathogenesis and also provide important insights into the current development of CHIKV and potential CHIKV vaccines for current development and clinical trials.